Investigating Iranian English language teachers’ wellbeing across their career stages - Ashegh Navaie, Leila; Gholami, Javad; Mohammadnia, Zhila (Frontiers in Psychology, 2024)
This study aims to investigate the wellbeing of Iranian English as Foreign Language (EFL) teachers across their career stages in terms of teaching experience. In this regard, the study categorized teachers into three groups based on their experience: novice, experienced, and highly experienced. Using a quantitative and cross-sectional survey design, this study employed a validated scale to measure psychological wellbeing, positive perception about self and life, goal setting and time management, and positive relationships among teachers. Using a convenience sampling procedure, 182 teachers participated in the study, representing varying age ranges, teaching experience, and employment status. The data was collected through an online survey within a month and underwent descriptive and inferential statistical analyses using SPSS software. The results revealed significant differences in the wellbeing of language teachers across experience groups. More specifically, novice teachers scored lower in various wellbeing dimensions than experienced and highly experienced teachers. These findings emphasize the importance of considering career stages when investigating teachers’ professional wellbeing. The findings also contribute to a deeper understanding of the relationship between teaching experience and wellbeing, with implications for supporting the EFL teachers’ wellbeing and informing educational policies and practices. The study results are discussed, and the related implications are provided for running professional development courses to enhance teachers’ wellbeing.